FACTORS INFLUENCING GOING-CONCERN AUDIT OPINIONS AND THEIR CONSEQUENCES: EVIDENCE FROM INDONESIAN LISTED FINANCIAL FIRMS - Afilia Damayanti; Munawar Muchlis; Roza Mulyadi (ZILLZELL MEDIA PRIMA, 2025)
This study aims to examine the antecedents of going concern audit opinions and their consequences for auditor switching among financial sector companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023. The independent variables include financial distress, audit committee effectiveness, and audit report lag. The dependent variable is the going concern audit opinion, and the consequence variable is auditor switching. A quantitative method was applied using logistic regression on a sample of 88 companies. Results indicate that financial distress and audit report lag significantly influence going concern opinions, whereas audit committee effectiveness has no significant impact. Furthermore, going concern opinions do not significantly affect auditor switching. These findings emphasize the importance of financial health and timely financial reporting in audit assessments and investor confidence.